The Sweet Land: Manufacturing "Tradition" in Small‐Town Bolivia. (20th June 2021) - Babel, Anna M.
Abstract : Chronotopes have been described as "envelopes" of time and space that provide the setting for the circulation of particular types of characters or personae (Silverstein 2005, Agha 2007, Bakhtin 1981, 1986). In this article, I investigate how these narratives of time and space are used to produce meaning in conjunction with structured relationships between groups of social categories, particularly discourses of tradition and modernity. Specifically, I examine the ways in which local actors shape and imagine how Saipina, a small town in central Bolivia, is represented to outside audiences. Influential actors produce a set of artifacts that represent the town, as well as a series of narratives that overlay values such as hard work and agricultural roots with goods such as sugarcane and chancaca, a raw sugar product, in representing the town to outside audiences.